Behind the trees, an opportunity to learn: the adoption of experience capitalization at the forest development department in Argentina - Tapella, Esteban; Naves, Natalia (Technical Centre for Agricultural and Rural Cooperation, 2019)
In the field of forestry development there are many experiences that are not sufficiently documented or shared. In order to encourage a critical reflection within such projects, and circulate the lessons learned, the National Department of Forest and Industrial Development at the Argentinean Ministry of Agriculture has held experience capitalization workshops with its staff. Positive results have led to the adoption of the approach in Mendoza.